The evolution of authoritarian rule in Algeria: linkage versus organizational power. Issue 8 (17th November 2019) - Hill, J. N. C.
ABSTRACT: This article draws on the Algerian regimes of Chadli Benjedid and Abdelaziz Bouteflika to critically evaluate Steven Levitsky and Lucan Way's dimension of linkage. The paper shows that, despite the intensification of the country's ties to the European Union (EU) from one regime to the other, the willingness and ability of Brussels to put democratizing pressure on Algiers decreased rather than increased. This development challenges Levitsky and Way's thesis and the importance they place on linkage in relation to their other dimensions of leverage and organizational power. The article concludes that: strengthening linkage does not always result in greater EU or Western democratizing pressure; the balance of importance Levitsky and Way strike between their dimensions is open to question; and, the EU has grown less willing to press for political change in Algeria.